Bond degradation of non-uniformly corroded steel rebars in concrete. (1st January 2021) - Fu, Chuanqing; Fang, Deming; Ye, Hailong; Huang, Le; Wang, Jiandong
Highlights: A detailed investigation on bond performance of non-uniform corrosion in concrete. A new impressed current method was used to induced non-uniform corrosion of rebar. The effects of longitudinal rib of rebar on corrosion and bon degradation are discussed. Abstract: In this work, the bond degradation of non-uniformly corroded steel rebars embedded in concrete was studied. A total of 105 concrete specimens with accelerated corrosion of steel rebar were evaluated using the pull-out test. The influences of corrosion mode, corrosion level, orientation of the longitudinal rib, and the position of steel rebar on the bond degradation were analyzed. The cracking patterns of corrosion-induced cracks, bond failure modes, and bond stress-slip relations were discussed. The results showed that the orientation of longitudinal rib and the thickness of concrete cover play a vital role in determining the cracking patterns of corrosion-induced cracks. In comparison to the uniformly corroded specimens, the bond performance of specimens with non-uniform corrosion of steel rebar degraded more significantly, and this phenomenon became even more pronounced as the corrosion level increased. Moreover, the beneficial improvements caused by the expansive rust on the bond performance were greatly dependent on the degrees of concrete constraint and corrosion level.